2000
DOI: 10.4049/jimmunol.165.2.1082
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Large Numbers of Virus-Specific CD8+ T Cells in HIV-Infected Progressors and Long-Term Nonprogressors

Abstract: The virus-specific CD8+ T cell responses of 21 HIV-infected patients were studied including a unique cohort of long-term nonprogressors with low levels of plasma viral RNA and strong proliferative responses to HIV Ags. HIV-specific CD8+ T cell responses were studied by a combination of standard cytotoxic T cell (CTL) assays, MHC tetramers, and TCR repertoire analysis. The frequencies of CD8+ T cells specific to the majority of HIV gene products were measured by flow cytometric detection of intracellular IFN-γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
193
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(209 citation statements)
references
References 74 publications
14
193
1
1
Order By: Relevance
“…This is lower than typically observed in other chronic viral infections such as in HIV-1, where the magnitude of HIV-1-specific IFN-␥ ϩ CD8 ϩ T cells ranges from 0.8% to 18.0%. 12,17 The magnitude of intrahepatic cytokine ϩ HBV-specific T cells was similar to that seen in cultured PBMC (0.0%-1.80%). The low magnitude of HBV-specific T cells found in blood was therefore not explained by sequestration of HBV-specific T cells to the liver, which has been previously shown to be true in both HBV and HCV infections when using virus-specific tetramer ϩ T cells.…”
Section: Discussionmentioning
confidence: 54%
“…This is lower than typically observed in other chronic viral infections such as in HIV-1, where the magnitude of HIV-1-specific IFN-␥ ϩ CD8 ϩ T cells ranges from 0.8% to 18.0%. 12,17 The magnitude of intrahepatic cytokine ϩ HBV-specific T cells was similar to that seen in cultured PBMC (0.0%-1.80%). The low magnitude of HBV-specific T cells found in blood was therefore not explained by sequestration of HBV-specific T cells to the liver, which has been previously shown to be true in both HBV and HCV infections when using virus-specific tetramer ϩ T cells.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, this sequential type of response has been reported during natural HIV infection with early strong responses often seen toward Nef and Env epitopes (29,30). Later, most HIV-infected patients, particularly LTNP patients, develop and maintain a broad response directed to multiple HIV Ags with a vast majority of cells responding to Gag and Pol (30,31). Our results with ⌬4SHIV KU2 DNA vaccine in mice demonstrated that an anti-HIV CD8 ϩ T cell response expanded the magnitude and breadth of T cell epitopes in a manner similar to natural HIV infection.…”
Section: Discussionmentioning
confidence: 90%
“…In the absence of treatment, different levels of viremia establish which probably represent different levels of antigenic stimulation on one hand, whereas increased frequencies of effective HIV-specific CD8 ϩ T cells may control viral replication on the other hand. These complex interactions between VL and CTL frequencies might preclude the detection of straightforward correlations (14,32,33). Third, it is likely that the amount of viral replication is controlled by the synergistic action of multiple immunological effector arms, including CD8 ϩ T cells (by means of cytolytic and noncytolytic mechanisms), CD4 ϩ T cells, antiviral neutralizing antibodies, and natural killer cells.…”
Section: Lack Of Correlation Between Plateau Vl and Magnitude Of Hiv-mentioning
confidence: 99%